2004
DOI: 10.1021/ol0498646
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of Long-Chain Polyketide Fragments by Reaction of 1,3-Dioxy-1,3-dienes with Allylsilanes:  Umpolung with Sulfur Dioxide

Abstract: [reaction: see text] In the presence of a Lewis or protic acid and at low temperature, 1,3-dioxy-1,3-dienes add to sulfur dioxide generating zwitterionic intermediates that can react with carbon nucleophiles such as allylsilanes. After a retro-ene elimination of SO(2), valuable polyketide precursors are obtained.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
22
0

Year Published

2004
2004
2010
2010

Publication Types

Select...
5
3

Relationship

3
5

Authors

Journals

citations
Cited by 27 publications
(23 citation statements)
references
References 23 publications
1
22
0
Order By: Relevance
“…[60][61][62][63][64] Neopentyl 1 H NMR spectra of the crude reaction mixtures, they were all better than 50%. In all cases the linear product 5a was favored (product of no allylic rearrangement).…”
Section: Resultsmentioning
confidence: 94%
See 1 more Smart Citation
“…[60][61][62][63][64] Neopentyl 1 H NMR spectra of the crude reaction mixtures, they were all better than 50%. In all cases the linear product 5a was favored (product of no allylic rearrangement).…”
Section: Resultsmentioning
confidence: 94%
“…Solvents after reactions and extraction were evaporated in a rotatory evaporator under vacuum (solvents were removed cooling at À20 C, in the case of low boiling point or low molecular mass compounds). TLC for reaction monitoring was performed on 60 3 , was transferred on the vacuum line to the MeCN solution frozen at À196 C. The mixture was allowed to melt and to warm to À40 C. After 30 min at this temperature but-2-enyl(trimethyl)silane (1c) …”
Section: Methodsmentioning
confidence: 99%
“…3-Acyloxy dienes were found to be good candidates. [12,19] As we had observed that the reactivity of the dienes and diastereoselectivity of the oxyallylation reaction fluctuate depending on small changes in the structure of diene, we decided to investigate this matter in more details. The synthesis should be designed so that it allows fast access to differently substituted C(1) and C(3) carbon atoms.…”
Section: Abstract In Frenchmentioning
confidence: 99%
“…[11] We have shown recently that enantiomerically enriched 1,3-dioxy-1,3-dienes of type 5 can be condensed with carbon-centered nucleophiles of type 6 in the presence of an excess of SO 2 and a catalytical amount of an acid promoter. [12,13] This generates b,g-unsaturated silyl sulfinates 7 that, after acidic workup, undergo quick desilylation and desulfation by means of a stereoselective retro-ene elimination of Abstract: In the presence of sulfur dioxide and an acid promoter, (À)-(1E,3Z)-2-methyl-1-((1S)-1-phenylethoxy)penta-1,3-dien-3-yl isobutyrate reacts with (Z)-3-(trimethylsilyloxy)-pent-2-ene giving a silyl sulfinate intermediate that undergoes, in the presence of palladium catalyst, a desilylation and retro-ene elimination of SO 2 with formation of (À)-(1Z,2S,3R,4S)-1-ethylidene-2,4-dimethyl-5-oxo-3-((1S)-1-phenylethoxy)-heptyl isobutyrate as major product. This ethyl ketone undergoes cross-aldol reaction with (2S)-2-methyl-3-[(tert-butyldimethylsilyl)-oxy]propanal giving an aldol that is reduced into a stereoheptad corresponding to the C(19)-C(27)-segment of Rifamycins with high diastereoselectivity and enantiomeric excess.…”
Section: Introductionmentioning
confidence: 99%
“…In situ oxidation of sulfinates 14 with Cl 2 or NCS provides the corresponding sulfonyl chlorides that can be reacted with primary and secondary amines to provide the corresponding sulfonamides 17, thus realizing a one-pot, four-component synthesis of polyfunctional suflonamides [60,61]. We review here applications of our reaction cascade 9 + SO 2 → 10 → 12 + 13 → 14 → 15 to the asymmetric total synthesis of polypropionate antibiotics [62] and disclose further chemistry of sultines with allylsilanes [63].…”
Section: Introductionmentioning
confidence: 97%